Listeriosis Prevention Knowledge Among Pregnant Women in the USA - Ruth Lynfield; Jay Schulkin; Elizabeth Kirkland; Joni Scheftel; Jeffery L. Jones; Folashade Ogunmodede (Hindawi Limited, 2005)
Background: Listeriosis is a food-borne disease often associated with ready-to-eat foods. It usually causes mild febrile gastrointestinal illness in immunocompetent persons. In pregnant women, it may cause more severe infection and often crosses the placenta to infect the fetus, resulting in miscarriage, fetal death or neonatal morbidity. Simple precautions during pregnancy can prevent listeriosis. However, many women are unaware of these precautions and listeriosis education is often omitted from prenatal care.